Social science as apologia. (August 2021) - Brandmayr, Federico
The social sciences are predominantly seen by their practitioners as critical endeavours, which should inform criticism of harmful institutions, beliefs and practices. Accordingly, political attacks on the social sciences are often interpreted as revealing an unwillingness to accept criticism and an acquiescence with the status quo. But this dominant view of the political implications of social scientific knowledge misses the fact that people can also be outraged by what they see as its apologetic potential, namely that it provides excuses or justifications for people doing bad things, preventing them from being rightfully blamed and punished. This introduction to the special issue sketches the long history of debates about the exculpatory and justificatory consequences of social science and lays the foundations for a theory of social scientific apologia by examining three main aspects: what social and cognitive processes motivate this type of accusation, how social theorists respond to it and whether different contexts of circulation of ideas affect how these controversies unfold.